The portuguese business cycle: chronology and duration dependence - Castro, Vítor (2015)
This paper tries to identify a chronology for the Portuguese business cycle and test for the presence of duration dependence in the respective phases of expansion and contraction. A duration-dependent Markov-switching vector autoregressive model is employed in that task. This model is estimated over year-on-year growth rates of a set of relevant economic indicators, namely industrial production, a composite leading indicator and, additionally, civilian employment. The estimated specifications allow us to identify four main periods of contraction during the last three decades and some evidence of positive duration dependence in contractions, but not in expansions, especially when employment is added to the model.